True statements:
a) x + y = y + x ⇒ commutative property of addition
b) (x * y) * z = x * (y * z) ⇒ associative property of multiplication
d) (x + y) + z = x + (y + z) ⇒ associative property of addition
False statements:
c) x - y = y - x should be: x - y = - y + x
e) (x - y) - z = x - (y - z) should be: (x - y) - z = x - (y + z)
Answer: 8y4+25y3+60y2+10y+7
Step-by-step explanation:
(y2+3y+7)(8y2+y+1)
=(y2+3y+7)(8y2+y+1)
=(y2)(8y2)+(y2)(y)+(y2)(1)+(3y)(8y2)+(3y)(y)+(3y)(1)+(7)(8y2)+(7)(y)+(7)(1)
=8y4+y3+y2+24y3+3y2+3y+56y2+7y+7
=8y4+25y3+60y2+10y+7
hope this helps!:)
Answer:
216π in²
Step-by-step explanation:
Base area = π × r²
36 π = π × r²
r² = 36
r = 6
Volume = base area × height
432 π = 36 π × height
height = 12
Surface area:
2 × π × r × (r + h)
2π × 6 × (6 + 12)
216π